Postnatal Blues- The Hong Kong Chinese Women’s Experiences - HAU, Florence WL (Hong Kong Journal of Gynaecology, Obstetrics and Midwifery, 2023)
The aim of this study is to explore the Hong Kong Chinese women’s experiences on postnatal blues and the potential role of midwives in helping these women. To achieve this aim, the study has adopted a qualitative method in the data collection and semi-structured interview was used. Eleven postnatal women who had been identified as having blues were interviewed either face-to-face or through telephone. They were asked to comment on their feelings and perceived needs at the time of blues. The interviews were tape-recorded and transcribed verbatim, first into Chinese and then English. Content analysis was carried out to identify themes and categories. The finding illustrated the women’s experience of blues, their perceived causes of the distress, and the mediating factors that contributed to their recovery. To conclude, the study has showed us a picture ofmisery of some of the postnatal women. Although the finding does not offer us a way to prevent the blues, but it does provide insight for midwives to help to alleviate the emotional distress of the postpartum women.